Predictors and Outcomes of SGLT2 Inhibitor Discontinuation in a Real-World Population after Hospitalization for Heart Failure - Masaki Nakagaito; Teruhiko Imamura; Ryuichi Ushijima; Makiko Nakamura; Koichiro Kinugawa (Biomedicines, 2023)
Background: Sodium–glucose cotransporter 2 inhibitors (SGLT2i) reduce mortality and morbidity in patients with heart failure (HF), but are discontinued in some patients. Such patients may not enjoy favorable benefits of SGLT2i therapy. We evaluated the risk factors for SGLT2i discontinuation in a real-world population with HF. Methods: We retrospectively included consecutive patients who were hospitalized for HF and administered SGLT2i during the index hospitalization between February 2016 and September 2021. We assessed the baseline clinical factors associated with post-discharge discontinuation of SGLT2i. Results: This study included a total of 159 patients (median age = 73 years, 57 women). Among baseline characteristics, a lower serum albumin level (odds ratio = 0.23, 95% confidence interval = 0.07–0.76, p = 0.016) and a higher dose of furosemide (odds ratio = 1.02, 95% confidence interval = 1.00–1.05, p = 0.046) were independently associated with the future discontinuation of SGLT2i following index discharge. Patients who terminated SGLT2i (n = 19) had a higher incidence of HF recurrence or cardiovascular death during the 1-year therapeutic period (32% versus 11%, p = 0.020). Conclusions: Among patients who initiated SGLT2i during hospitalization for HF, lower serum albumin levels and higher doses of loop diuretic at index discharge were associated with the discontinuation of SGLT2i following index discharge. We should pay special attention to patients with such characteristics during the initiation of SGLT2i and during SGLT2i therapy.